Cannabis and Rheumatoid Arthritis: A Scoping Review Evaluating the Benefits, Risks, and Future Research Directions - Nicole Paland; Haya Hamza; Antonina Pechkovsky; Miran Aswad; Dayana Shagidov; Igal Louria-Hayon (Rambam Maimonides Medical Journal, 2023)
Rheumatoid diseases, including rheumatoid arthritis, osteoarthritis, and fibromyalgia, are characterized by progressive inflammation in the musculoskeletal system, predominantly affecting the joints and leading to cartilage and bone damage. The resulting pain and ongoing degradation of the musculoskeletal system contribute to reduced physical activity, ultimately impacting quality of life and imposing a substantial socioeconomic burden. Unfortunately, current therapeutics have limited efficacy in slowing disease progression and managing pain. Thus, the development of novel and alternative therapies is imperative. Cannabinoids possess beneficial properties as potential treatments for rheumatoid diseases due to their anti-inflammatory and analgesic properties. Preclinical studies have demonstrated promising results in halting disease progression and relieving pain. However, there is a scarcity of patient clinical studies, and the available data show mixed results. Consequently, there are currently no established clinical recommendations regarding the utilization of cannabis for treating rheumatoid diseases. In this review, we aim to explore the concept of cannabis use for rheumatoid diseases, including potential adverse effects. We will provide an overview of the data obtained from preclinical and clinical trials and from retrospective studies on the efficacy and safety of cannabis in the treatment of rheumatoid diseases.